Determination of the target parameters using the Monte Carlo method for an experiment on inelastic neutron scattering in different samples at the "TANGRA" installation - Dabylova, S; Kopatch, Yu. N.; Sakhiev, S. K.; Grozdanov, D. N.; Fedorov, N. A. (Eurasian Journal of Physics and Functional Materials, 2026)
Using the tagged neutron method at the "TANGRA" facility at Frank Laboratory of Neutron Physics of the Joint Institute for Nuclear Research based on the ING-27 standard neutron generator, a study of the 14.1 MeV inelastic neutron scattering reaction on different nuclei was carried out. The angular distributions of g-quanta accompanying inelastic neutron scattering on atomic nuclei were measured. This article presents a GEANT4-based program that allows calculating the interaction of fast neutrons with matter and simulating the experiment and also presenting the results of the experiment in a convenient and visual form. Using the written program, optimal target parameters were determined. The algorithm used by the program is given in this work. The general description of the experimental installation, data collection and processing systems is given. Recommended Citation Dabylova, S. B.; Kopatch, Yu. N.; Sakhiev, S. K.; Grozdanov, D. N.; and Fedorov, N. A. (2020) "Determination of the target parameters using the Monte Carlo method for an experiment on inelastic neutron scattering in different samples at the "TANGRA" installation," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 4. DOI: https://doi.org/10.29317/ejpfm.2020040304